1999
DOI: 10.1108/02683949910263837
|View full text |Cite
|
Sign up to set email alerts
|

A construct‐oriented analysis of individual‐level polychronicity

Abstract: This paper provided construct validity evidence for polychronicity in two related studies. Study 1 assessed the relationship between individuals' stated polychronicity preferences and peer ratings of polychronicity in a multitrait-multimethod design, which indicated that different raters were able to agree about an individual's polychronicity. Additional construct validity evidence was provided by linking polychronicity to several potentially related constructs such as achievement striving, impatience/irritabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 31 publications
1
71
1
1
Order By: Relevance
“…This discomfort can be reduced by modifying the preferences. In our case, this means that a person who is forced to work in multitasking way but who would prefer not to do so may change his or her preference, becoming more polychronic (see Conte et al, 1999, for a similar argument). However, this idea rests on the assumption that polychronicity can change -something not all polychronicity researchers believe (e.g., Cotte & Ratneshwar, 1999) and which may be in conflict with the fairly high re-test reliabilities for polychronicity (e.g., .78 over a 2-month interval, ; see also Bluedorn et al, 1999).…”
Section: Alternative Antecedents Of Polychronicitymentioning
confidence: 99%
“…This discomfort can be reduced by modifying the preferences. In our case, this means that a person who is forced to work in multitasking way but who would prefer not to do so may change his or her preference, becoming more polychronic (see Conte et al, 1999, for a similar argument). However, this idea rests on the assumption that polychronicity can change -something not all polychronicity researchers believe (e.g., Cotte & Ratneshwar, 1999) and which may be in conflict with the fairly high re-test reliabilities for polychronicity (e.g., .78 over a 2-month interval, ; see also Bluedorn et al, 1999).…”
Section: Alternative Antecedents Of Polychronicitymentioning
confidence: 99%
“…Additional research has revealed a relationship among time urgency, polychronicity, and achievement strivings. That is, individuals driven for success often take on more than one task at a time, performing with a sense of urgency in accomplishing their goals (Conte, Rizzuto, & Steiner, 1998).…”
Section: Personality Factorsmentioning
confidence: 99%
“…Existing research has linked polychronicity to a variety of differences in personality (for example, Conte & Gintoft, 2005;Conte & Jacobs, 2003;Conte et al, 1999;Ishizaka et al, 2001;Kantrowitz, Grelle, Beaty & Wolf, 2012;Schell & Conte, 2008;Taylor, Locke, Lee & Gist, 1984). Although the research examining the relationship between polychronicity and personality is somewhat limited, existing findings show that polychronicity is related to a variety of non-cognitive predictors, including some dimensions of the Big Five conceptualization of personality.…”
Section: Polychronicitymentioning
confidence: 97%
“…Another study found perceived fit of polychronicity between the individual and the organization to be related to job satisfaction (Arndt et al, 2006). It is thought that to the extent possible, individuals manage workloads and seek work environments in accordance with their preferences for polychronicity (Conte et al, 1999).…”
Section: Polychronicitymentioning
confidence: 99%
See 1 more Smart Citation